Black Turpentine Beetle, Dendroctonus terebrans (Olivier) (Insecta: Coleoptera: Curculionidae: Scolytinae) - Albert E. Mayfield; John L. Foltz (EDIS)
The black turpentine beetle, Dendroctonus terebrans (Olivier), or BTB, is one of five common species of pine bark beetles in the southeastern United States. Black turpentine beetles bore into the inner bark of stressed or injured pines (Pinus spp.), where they breed and feed on phloem tissue. Adults are strongly attracted to volatile pine odors and readily breed in fresh stumps. Attacks on standing trees usually occur on the lower 1 to 2 m of the trunk or on large roots. Light attacks may kill only localized sections of phloem tissue, but numerous attacks per stem result in tree mortality. Infestations commonly occur in pine stands affected by recent logging activity (e.g., thinning), fire, mechanical injury, storm damage, climatic stress, or competition (USDA Forest Service 1985, Dixon 1986). This document is EENY-356, one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date September 2005.